Adaptive potential of durum wheat (Triticum durum Desf.) varieties of Azerbaijan - Kh. N. Rustamov; Z. I. Akparov; M. A. Abbasov (Труды по прикладной ботанике, генетике и селекции)
Background. Studies into the adaptability of the genetic diversity of cultivated plants and their wild relatives to various environments are induced by global climate change. Introduction of adaptive wheat cultivars resistant to environmental stressors is the basis for stable harvests. This article presents the results of a research into the adaptive value of indigenous durum wheat varieties and improved cultivars released in different years in Azerbaijan.Materials and methods. The experiments were carried out in the foothills of Mountainous Shirvan under unsecured non-irrigation at Gobustan Experiment Station of the Research Institute of Crop Husbandry. In 2012–2014, contrasting in weather conditions, levels and structure of yield were analyzed. VIR’s guidelines were used to study 42 durum wheat varie ties, including 10 landraces. The years of study differed sharply in rainfall. Selyaninov’s hydrothermal coefficient was used to assess the conditions of growing seasons.Results. Mostly modern cultivars of the semi-intensive type were distinguished for a set of agrobiological traits. Adaptability coefficients (0.81–1.23) showed that the response of the studied varieties to unfavorable conditions was highly expressed. Indigenous landraces ‘Ag bughda’ and ‘Bozak’, old breeding varieties ‘Arandani’, ‘Ag bughda 13’, ‘Kahraba’ and ‘Mirbashir 50’, and new cultivars ‘Karagilchig 2’ and ‘Barakatli 95’ had the highest adaptability coefficients. The first of them demonstrated stable yield, and the latter two were also resistant to stressors.Conclusion. Durum wheat yields under the conditions of moderately continental climate in Mountainous Shirvan depended on the number and weight of grains per ear. The varieties identified for the best adaptability are recommended to be included in crosses to develop new plastic cultivars of durum wheat.